PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI BERBASIS GAME HAGO PADA MATERI VIRUS KELAS X SMA - Bella Anggraini; Vlorensius Vlorensius; Zulfadli Zulfadli (Biopedagogia, 2020)
The purpose of this study is to analys the quality of monopoly based on Game Hago. The Hago Game-based monopoly on virus material for class X SMA is very feasible as a learning medium with the percentage of material experts being 84% (very feasible), media experts being 96% (very feasible). Game-based monopoly Hago gets a response from expert practitioners who are teachers of Biology subjects at the Hang Tuah Tarakan High School of 94% (very feasible) and student responses using Hago Game-based Monopoly learning media are 92% (very good). Keywords:  Monopoly based on Hago Game, Quality